2021
DOI: 10.1111/jace.17745
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of cubic tricalcium aluminate in the presence of calcined clays

Abstract: Calcium sulfates take an important role in the reaction of pozzolanic materials by forming ettringite with aluminum ions from the pozzolan. 1 Sulfate carriers like gypsum, bassanite, or anhydrite are used to retard the tricalcium aluminate (C 3 A) reaction in ordinary portland cement (OPC). 2 The latter mechanism is used to avoid flash set and to optimize strength development by preventing a superposition of the silicate and aluminate clinker reaction. 3 As calcined clay blended cements 4 or limestone calcined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…In comparison, no clear aluminate peak could be identified in the metasmectite-rich samples due to the further addition of gypsum, already indicating a too high sulfate dosage for these systems. The lower sulfate requirement for 2:1 compared to 1:1 meta-phyllosilicates is in line with previous studies [ 26 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison, no clear aluminate peak could be identified in the metasmectite-rich samples due to the further addition of gypsum, already indicating a too high sulfate dosage for these systems. The lower sulfate requirement for 2:1 compared to 1:1 meta-phyllosilicates is in line with previous studies [ 26 ].…”
Section: Resultssupporting
confidence: 92%
“…The great potential of CC is based on physical effects such as the filler effect [ 22 , 23 ] and the adsorption of ions from the pore solution [ 24 ], as well as on the release of silicon and aluminum ions at an early time of hydration [ 15 , 25 ]. This is evidenced by a strong influence of the early clinker hydration in CC blended systems [ 26 , 27 , 28 ]. The released aluminum exploits its full potential, especially in the presence of LP [ 18 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that other surfaces can contribute to the sulphate adsorption process. A recent study [106] reported the faster occurrence of the C 3 A hydration peak in C 3 Agypsum-calcined clay systems. Due to the lack of calcium silicate phases in this system, this cannot be attributed to sulphate uptake from C-S-H, or reaction of calcined clays (due to the lack of portlandite).…”
Section: Sulphate Adjustmentmentioning
confidence: 94%
“…When comparing 1:1 to 2:1 phyllosilicate dominated clays, the main difference lies in the availability of aluminum. At later hydration ages aluminum-rich clays can lead to higher amounts of AFm phases and the formation of strätlingite [44][45][46] as well as during the first day in systems without silicate clinker reaction [33].…”
Section: Reaction Kinetics and Phase Formationmentioning
confidence: 99%